Reconstructing the Protections of Women’s Rights Under Islamic Law in the Context of Contemporary Challenges to Gender Equality - Muhammadong Muhammadong (Jurnal Ilmu Sosial dan Humaniora, 2026)
Recent developments in the discussion of gender equality have presented substantial challenges to the understanding and implementation of the Islamic legal protection of women’s rights. The purpose of this study is to study the notion of women’s rights protection in Islamic law and to reconstruct the legal framework of this notion to preserve its application in the resolution of the issues of gender equality in the present time without prejudice to the basic principles of Sharia. The study uses statutory, conceptual, and Islamic legal methods in the context of normative legal research technique. The main legal sources are the Qur’an, Hadith and relevant laws while the secondary sources are scholarly publications, peer-reviewed journal articles and other academic papers. Qualitative analysis of the evidence was performed by legal interpretation and doctrinal analysis. The findings reveal that the preservation of women’s rights under Islamic law is based on the concepts of fairness (al-’adl), public interest (maslahah), equality of human dignity, and the protection of fundamental rights. Nevertheless, patriarchal sociocultural notions and textualist readings nevertheless hinder its application, therefore preventing substantive justice. Therefore, the reconstruction of Islamic law requires contextual interpretation, the maqāṣid al-sharī'ah and adaptive ijtihad so as to cope with modern social changes. The study indicates that the protection of women’s rights in Islamic law must be reconstructed to promote substantive gender justice and respect for the universal principles of Sharia. Islamic law will so provide flexible, inclusive and equitable legal protection in modern society.